The Life and Work of George Boole : A Prelude to the Digital Age - MacHale, Desmond (Book collections on Project MUSE., 2014)
This book, aimed at the general reader and now available again, is the first full-length biography of George Boole (1815-1864) who has been variously described as the founder of pure mathematics, one of the fathers of computer science and discoverer of symbolic logic.